A Selected Guide to Government Agencies Concerned with Exceptional Children - Glassman, Lynne, Comp.; Erickson, Donald, Comp.; Special Education IMC/RMC Network, Arlington, VA. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
The selected guide to government agencies involved with exceptional children is based on data available as of April, 1971. (For a companion guide, see EC 042 251.) For each agency listed, the following information is provided where applicable: agency name, a brief explanatory statement about the agency and its responsibilities, center and director address, telephone number, region served, operational centers, planning centers, evaluation centers, and training centers. Coverage of the Special Education Instructional Materials Center/Regional Media Center Network include the Network office, Special Education Instructional Materials Centers, Regional Media Centers, and associate centers. Listed next is the United States Office of Education (USOE), Bureau of Education for the Handicapped Sponsored Programs, which includes various centers. Other USOE programs noted are the Bureau of Educational Personnel Development and the National Center for Educational Research and Development Sponsored Programs. Additional Department of Health, Education and Welfare Programs for the Handicapped mentioned are Social Rehabilitation Services and Public Health Service. Entered last are executive committees and the President's Task Forces. (CB)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Agencies; Directories; Exceptional Child Services; Gifted; Government Role; Handicapped Children; National Programs; Public Agencies; Regional Programs